Odpowiedzi

Najlepsza Odpowiedź!
2010-03-06T16:06:38+01:00
Odp 1
x³-6x²+12x-8-6x+3x²=x³-3x²+10
6x=18
x=3
odp 2
x/5+3=⅔+x+1/5 /*15
3x+45=10+15x+3
12x=32
x=2 i 2/3




2010-03-06T16:12:13+01:00
A)
(x-2)³-3x(2-x)=x²(x-3)+10
(x -2)²(x -2) +3x(x -2) = x² ( x -3) + 10
(x -2)[( x -2)² +3x] = x³ -3x² +10
(x-2)[ x² -4x +4 +3x] = x³ -3x² +10
(x-2) (x² -x +4) = x³ -3x² +10
x³ -x² +4x -2x² +2x -8 -x³ +3x² -10 = 0
+6x -18 = 0
6x = 18
x = 18 :6
x = 3

b)x/5+3=⅔+x+1/5 /15
3x + 45 = 10 + 15x +3
3x -15x = 13 -45
-12x = - 32
x = (-32): (-12)
x = 2 i 8/12
x = 2 i 2/3